Exploring the link between Facebook intensity and online political participation: a study on Malaysian youth - Tham, Jen Sern; Wong, Kay Chern (Human Resource Management Academic Research Society (HRMARS), 2023)
With these technological advancements, our lifestyles are significantly affected by the advent of the Internet. The emergence of social media makes our life easier by saving time and cost. Besides that, social media enables a new form of political participation. Although the level of political involvement among the youth is relatively low in Malaysia due to several factors, social media provides a unique platform for the youth to express their views and participate in politics. Thus, this study has been conducted to examine the relationship between Facebook Intensity and online political participation. The factors that contribute to the level of online political participation will also be studied. This study has been conducted using a quantitative research method by designing a questionnaire. The target population of this study is the local undergraduate students from the Faculty of Modern Languages and Communication, Universiti Putra Malaysia. A simple random sampling technique was used, and 150 respondents were involved in this study. The collected data were analysed using Statistical Package for the Social Science (SPSS). Based on the results, there is a significant positive relationship between Facebook Intensity and online political participation. At the same time, there are no relationships between interactivity with political figures, political interest and online political participation among the youth. Facebook Intensity is the main contributor to encouraging the youth to participate in politics online in this study.